Da formação em ballet à atuação em dança: a práxis criadora como caminho de superação - Fátima, Cíntia Regina de (2015)
This study aimed to apprehend the senses and meanings that a ballet teacher assign to his formation and action process (as a ballet dancer as a teacher). Therefore, a ballet dancer (Rodolfo) was selected, dance teacher (that taught ballet by a period) in a private institution and in a social project. An interview was done, in a public place, which searched to apprehend the participant´s history life. The interview was recorded and the audio was transcript accordingly with participant's authorization. To analyze data various interviews readings were done searching its content in its totality and, in the same time, it was indicated themes (formation and action) and subthemes that answered to the study objectives. Data were taken through historic-dialectic materialism. From analyzes it is possible to infer that Rodolfo had a formation and action process permeated by contradictions: from ballet interest to the conflict among parents, he was supported by his father opposing his mother; from the absence of a ballet school, to the difficulties to attend classes in other city; from his evolvement to the prejudice of his mates; from an activity cosmopolitan to the prejudices of a small city inhabitants; from the renunciation of study out to a course available in his region; from the mother that was opposite to his ballet formation to the mother that gives him conditions for professional acting; from ballet rigidity to the liberty discovery of modern and contemporaneous dance; from moving from a small city to the metropolis; from the crisis provoked by a familiar tragedy to the contact with social inequality; from depression to the new senses to his life through teaching activity. They are critical moments that produce new senses and meanings to Rodolfo´s life, to dance and to teaching. Contradictions that take to overcoming, sometimes perceived as luck , sometimes critically conscious. It is possible to conclude that dance (or ballet itself) can be an effective way of overcoming social determinations, not in sense of alienation, but as a cathartic possibility, it means felling transformation